Empagliflozin for heart failure with preserved left ventricular ejection fraction with and without diabetes - Filippatos, Gerasimos; Butler, Javed; Farmakis, Dimitrios; Zannad, Faiez; Ofstad, Anne Pernille; Ferreira, João Pedro; Green, Jennifer B.; Rosenstock, Julio; Schnaidt, Sven; Brückmann, Martina; Pocock, Stuart J.; Packer, Milton; et al. (Circulation, 2022)
Background: Empagliflozin improves outcomes in patients with heart failure with a preserved ejection fraction, but whether the effects are consistent in patients with and without diabetes remains to be elucidated. Methods: Patients with class II through IV heart failure and a left ventricular ejection fraction >40% were randomized to receive empagliflozin 10 mg or placebo in addition to usual therapy. We undertook a prespecified analysis comparing the effects of empagliflozin versus placebo in patients with and without diabetes. Results: Of the 5988 patients enrolled, 2938 (49%) had diabetes. The risk of the primary outcome (first hospitalization for heart failure or cardiovascular death), total hospitalizations for heart failure, and estimated glomerular filtration rate decline was higher in patients with diabetes. Empagliflozin reduced the rate of the primary outcome irrespective of diabetes status (hazard ratio, 0.79 [95% CI, 0.67, 0.94] for patients with diabetes versus hazard ratio, 0.78 [95% CI, 0.64, 0.95] in patients without diabetes; Pinteraction=0.92). The effect of empagliflozin to reduce total hospitalizations for heart failure was also consistent in patients with and without diabetes. The effect of empagliflozin to attenuate estimated glomerular filtration rate decline during double-blind treatment was also present in patients with and without diabetes, although more pronounced in patients with diabetes (1.77 in diabetes versus 0.98 mL/min/1.73m2 in patients without diabetes; Pinteraction=0.01). Across these 3 end points, the effect of empagliflozin did not differ in patients with prediabetes or normoglycemia (33% and 18% of the patient population, respectively). When investigated as a continuous variable, baseline hemoglobin A1c did not modify the effects on the primary outcome (Pinteraction=0.26). There was no increased risk of hypoglycemic events in either subgroup as compared with placebo.Conclusions: In patients with heart failure and a preserved ejection fraction enrolled in the EMPEROR-Preserved (Empagliflozin Outcome Trial in Patients With Chronic Heart Failure With Preserved Ejection Fraction), empagliflozin significantly reduced the risk of heart failure outcomes irrespective of diabetes status at baseline.
Gesehen am 17.10.2023